A 28 GHz MIMO antenna array design for 5G applications - Habaebi, Mohamed Hadi; Che Mustapha, Nurul Arfah; Janat, Mohanad; Islam, Md. Rafiqul (Institute of Advanced Scientific Research, 2019)
In this paper, an in-depth study on the designing of a compact 2x2 MIMO planar antenna array, that consists of 4 subarrays with each subarray having 4 rectangular patch elements with the main beam gain at boresight of 13.4 dB and with impedance bandwidth of 500 MHz at frequency of 28 GHz, is presented. The antenna array resonates at centre frequency of 28 GHz supporting mmWave frequency range expected to be utilized in the upcoming 5G. To combat challenges inherent to the mmWave band, the antenna array sits on a metamaterial substrate to reduce inter spacing between antenna array elements, shrink the size and obtain high gain. The antenna array was designed and simulated by computer simulation technology (CST 2016). Parameters taken into consideration, for the antenna array performance analysis, are scattering coefficients, correlation coefficient, and the mean effective gain (e.g., diversity gain). Subarrays 1 and 4 form the first MIMO element, and subarrays 2 and 3 form the second MIMO element. The simulations results are promising to show that MIMO elements are quite independent(>40dB isolation). The design packs 16 antenna elements into a mere 32.65x38.08 mm2 surface area only.